The role of extrusions and intrusions in fatigue crack initiation. (November 2017) - Polák, J.; Mazánová, V.; Heczko, M.; Petráš, R.; Kuběna, I.; Casalena, L.; Man, J.
Highlights: Profiles of persistent slip markings (PSMs) in four fatigued materials using FIB cutting. Surface lamella production for TEM with undamaged surface. Documentation of the shape of PSMs as extrusions and extrusion-intrusion pairs. Observation of surface profile and underlying dislocation structure of persistent slip bands. Observation and documentation of fatigue crack initiation from the tip of intrusions. Implication of experimental findings to the models of fatigue crack initiation. Abstract: The profiles of persistent slip markings produced by uniaxial and biaxial cyclic straining in four different polycrystalline materials with f.c.c. structure were investigated using focused ion beam (FIB) cutting and TEM observation of oriented surface foils. Typical shapes of persistent slip markings are extrusions accompanied by parallel intrusions. In some cases only extrusions were developed and intrusions were produced later in fatigue life. In polycrystalline copper extrusions and intrusions appear on the surface of the grain where persistent slip band characterized by ladder-like dislocation structure egress on the surface. Similar features were observed in fatigued austenitic 316L and Sanicro 25 steels but the extrusion and intrusion shapes were more complicated. Crack-like intrusion shapes produce high stress and strain concentration and primary stage I crack starts to grow from the tip of intrusions. The experimental observations were compared with the predictions of the existing crack initiation models.